PENGEMBANGAN E-MODUL INTERAKTIF BERBASIS ARTICULATE STORYLINE 3 PADA MATERI KINEMATIKA DI KELAS XI SMAN 12 PADANG - Aidil Fajri; Aidhia Rahmi; Megasyani Anaperta (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Physics learning in senior high schools still faces several challenges, including the dominance of teacher-centered instruction, limited interactive learning media, and low student engagement. These conditions affect students’ interest and conceptual understanding, especially in kinematics, which is considered abstract. This study aims to develop an interactive e-module based on Articulate Storyline 3 for kinematics material in Grade XI of SMA Negeri 12 Padang and to examine its validity and practicality. This research employed the Research and Development (R&D) method using the ADDIE development model, consisting of analysis, design, development, implementation, and evaluation stages. The research subjects included material and media experts, a physics teacher, and Grade XI students. Data were collected using validation sheets and practicality questionnaires. The results showed that the developed e-module achieved a validity score of 92.27% (very valid category) and a practicality score of 85.04% (very practical category). Therefore, the interactive e-module based on Articulate Storyline 3 is feasible to be used as an alternative learning resource to enhance the quality and effectiveness of physics learning.